Low TSH and low T3 hormone levels as a prognostic for mortality in COVID-19 intensive care patients - Sror-Turkel, Or; El-Khatib, Nidal; Sharabi-Nov, Adi; Avraham, Yaniv; Merchavy, Shlomo (Frontiers in Endocrinology, 2024)
COVID-19 can cause both pulmonary and systemic inflammation, potentially determining multi-organ dysfunction. The thyroid gland is a neuroendocrine organ that plays an important role in regulating immunity and metabolism. Low serum levels of thyroid hormones are common in critical disease situations. The association between low thyroid hormone levels and mortality in COVID-19 intensive care patients has yet to be studied. Aim: To compare thyroid hormone levels between patients in the general intensive care unit (ICU) to patients in the COVID-19 intensive care unit. Methods: A retrospective comparative study of 210 patients who were hospitalized at Ziv Medical Center in the general intensive care unit and in the COVID-19 intensive care unit. Clinical and demographic data were collected from patient's electronic medical records. Results: Serum thyroid hormone levels of TSH, T4 and T3 were significantly lower in COVID-19 intensive care unit patients35 compared to the patients from the general intensive care unit (p<0.05). The mortality rate in the COVID-19 ICU (44.4%) was higher compared to the general ICU (27.3%) (p <0.05). No significant statistical difference was observed between the two groups in terms of gender and recorded comorbidities of diabetes Mellitus, cerebral vascular accident (CVA), kidney disease and cancer. Conclusions: Low serum thyroid hormone levels -T3, T4 and TSH in COVID-19 ICU patients are associated with higher mortality and could possibly be used as a prognostic factor for mortality among COVID-19 ICU patients. Thyroid hormone levels should be a part in the routine evaluation of COVID-19 ICU patients.